Perbandingan Fatwa-Fatwa Ulama Tentang Jual Beli Non-Fungible Token (NFT) - Lola Abellia; Moetia Septi; M. Indra; Muhammad Gilang Aidil Saputra; Saiin, Asrizal (El-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2025)
This study aims to analyze Islamic scholars' fatwas regarding the sale and purchase of Non-Fungible Tokens (NFTs) from a sharia economic perspective. On the one hand, NFTs offer economic opportunities through ownership of non-duplicable digital assets. On the other hand, concerns have arisen regarding the validity of transactions, the potential for speculation, and their compliance with sharia principles such as clarity of contracts, benefits (manfa'ah), and freedom from gharar (uncertainty) and maysir (speculation/gambling). This study uses a qualitative analysis method with a library research approach, specifically content analysis of fatwas, opinions of contemporary scholars, and classical and modern fiqh literature. The results show differences of opinion among Islamic scholars. Some permit NFT transactions under certain conditions, such as clear benefits and a lawful object, while others consider NFTs to carry high speculative risks and uncertainty. These differences are influenced by understandings of the substance of NFTs as contract objects and the context in which they are used. This article concludes that caution is essential in NFT transactions. Furthermore, clear regulations and guidance from sharia authorities are needed to ensure that NFT trading practices are conducted in accordance with Islamic economic principles, thus providing fair, transparent benefits, and free from prohibited practices.